Ah, 3n squared is a beautiful mathematical expression. It simply means you take the number n, square it (multiply it by itself), and then multiply that result by 3. Isn't that just lovely? Just imagine all the wonderful possibilities you can create with this simple equation.
Oh, dude, like, 3n times n is just 3n^2. It's like, you take 3 times n, and then multiply that by n again. So, it's basically n squared, but with a 3 in front. Easy peasy, lemon squeezy.
3n+2+3n+2=6n+4
9
3n+5n=8n
3n = 0.138 n = 0.046
The GCF is 3n.
3n2-8n+4 = (3n-2)(n-2) when factored
3(3n - 1)(n + 1)
Oh, dude, like, 3n times n is just 3n^2. It's like, you take 3 times n, and then multiply that by n again. So, it's basically n squared, but with a 3 in front. Easy peasy, lemon squeezy.
It's kind of tough to look for the 'answer', because it's not even clear what the question is.All I can think of is: Somebody tells you what 'n' is, and then you're supposed tofigure out what number 5('n' squared + 3n) is. If that's the question, then of courseyou need to know what 'n' is before you can start on it.I'm, not at all sure that that's the question, but it's all I can think of, so here's an example:Let's say that 'n' is 1 .n2 = 13n = 3n2 + 3n = 45('n' squared + 3n) = 54 = 625That may not be too helpful, because, as I said above, the way you postedthe question, I can't see what the 'problem' (the assignment) is.
If that's n squared, the multiples are n squared, 2 n squared, 3 n squared and so on. If that's n + 2, the multiples are n + 2, 2n + 4, 3n + 6 and so on.
3n2 - 7n = 0 n(3n - 7) = 0 So either n = 0 or 3n-7 = 0 ie, either n = 0 or n = 7/3 = 21/3 = 2.33...
(3n)(3n-1) = 3n * 3n - 3n * 1 Now, perform the multiplication: (3n * 3n) = 9n^2 (3n * 1) = 3n So, (3n)(3n-1) simplifies to: 9n^2 - 3n
To find the answer to the expression 7n - 2 - 3n + 4, you first simplify by combining like terms. Combine the 7n and -3n terms to get 4n. Then, combine the -2 and +4 terms to get +2. Therefore, the final answer is 4n + 2.
(8m - 3n)^2 I assume you mean 'squared' , when you write 'square 2'. Because means raising to the power of '2'. Whereas 'cubing' means raising to the power of '3'. To answer (8m - 3n)(8m - 3n( = 64m^2 - 24mn - 24 mn + 9n^2 = 64m^2 - 48 mn + 9n^2 Done!!!!
3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6
FORMULA: (n [squared] -- 3n) / 2 (18 [squared] -- 3 x 18) / 2 = (324 -- 54) / 2 = 270 / 2 = 135 Easy as Pi ;)